Pilot of a dog-walking program to foster and support community inclusion for people with cognitive disabilities. Issue 3 (30th January 2023) - Bould, Em; Callaway, Libby; Warren, Narelle; Lalor, Aislinn; Burke, Joanne
Abstract: Purpose: To evaluate a dog-walking program (called "Dog Buddies") designed to address the need for evidence-based programs that create opportunities for people with cognitive disabilities to be more socially included in mainstream society. The research question was: Does community dog walking foster social interaction for people with cognitive disabilities? Materials and methods: Single-case experimental design was used with four individuals (three with intellectual disability; one with Acquired Brain Injury (ABI)) recruited via two disability service providers in Victoria. Target behaviours included frequency and nature of encounters between the person with disability and community members. Change was measured from baseline (five community meetings with a handler but no dog) to intervention period (five meetings minimum, with a handler and a dog). Semi-structured interviews, audio-recorded and transcribed verbatim, provided three participants' subjective experiences of the program. Results: Dog Buddies increased the frequency of encounters for all participants. The presence of the dog helped to foster convivial encounters, community members were found to be more welcoming, and some participants were recognised or acknowledged by name over time in the intervention phase. Conclusions: The dog-walking program offered a simple means of influencing the frequency and depth of community-based social interactions for people with cognitive disabilities. IMPLICATIONS FOR REHABILITATION: The co-presence of people with disabilities in the community with the general population does not ensure social interaction occurs. Both disability policy, and the programs or support that is provided to people with disabilities, needs to have a strong commitment to the inclusion of people with disabilities in mainstream communities. Dog Buddies is a promising example of a program where the presence of a pet dog has been demonstrated to support convivial, bi-directional encounters of people with cognitive disabilities and other community members. Dog-walking offers a simple means of influencing the frequency and depth of community-based social interactions for people with cognitive disabilities.